Interindividual and Regional Variability in Drug Transporter Abundance at the Human Blood–Brain Barrier Measured by Quantitative Targeted Proteomics. Issue 1 (18th March 2019) - Billington, Sarah; Salphati, Laurent; Hop, Cornelis E. C. A.; Chu, Xiaoyan; Evers, Raymond; Burdette, Doug; Rowbottom, Christopher; Lai, Yurong; Xiao, Guangqing; Humphreys, W. Griffith; Nguyen, Tot Bui; Prasad, Bhagwat; et al.
Abstract : For in vitro to in vivo extrapolation (IVIVE) of brain distribution of drugs that are transported at the human blood–brain barrier (BBB), it is important to quantify the interindividual and regional variability of drug transporter abundance at this barrier. Therefore, using quantitative targeted proteomics, we compared the abundance of adenosine triphosphate–binding cassette and solute carrier transporters in brain microvascular endothelial cells (BMECs) isolated from postmortem specimens of two matched brain regions, the occipital (Brodmann Area (BA)17) and parietal (BA39) lobe, from 30 adults. Of the quantifiable transporters, the abundance ranked: glucose transporter (GLUT)1 > breast cancer resistance protein > P‐glycoprotein (P‐gp) > equilibrative nucleoside transporter (ENT)1 > organic anion‐transporting polypeptide (OATP)2B1. The abundance of multidrug resistance protein 1/2/3/4, OATP1A2, organic anion transporter (OAT)3, organic cation transporter (OCT)1/2, OCTN1/2, or ENT2 was below the limit of quantification. Transporter abundance per gram of tissue (scaled using GLUT1 abundance in BMEC vs. brain homogenate) in BA17 was 30–42% higher than BA39. The interindividual variability in transporter abundance (percentage of coefficient of variation (%CV)) was 35–57% (BA17) and 27–46% (BA39). These data can be used in proteomics‐informed bottom‐up IVIVE to predict human brain drug distribution.